The Relationship of Patient Satisfaction with Therapeutic Services with Therapeutic Compliance in Outpatient Hypertension Patients at Wonosari Hospital - Dewi Ratih Anggraini (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2022)
The increasing prevalence of hypertension cases is related to the low level of patient compliance in taking antihypertensive drugs. So, adherence to therapy is an essential element in managing hypertensive patients. One of the efforts to improve patient compliance in the use of drugs is the need for good service quality toprovide satisfaction to patients with the therapeutic services obtained. This study aimed to determine the relationship between satisfaction with therapy services and adherence to therapy in outpatient hypertension patients at Wonosari Hospital. The type and research design used is analytic observational with a cross-sectionalapproach. The number of samples was determined using the Lemeshow formula. The sampling technique used in this study is nonprobability sampling with the purposive sampling method. The sample subjects used in the study were all patients with a primary diagnosis of hypertension who had met the inclusion and exclusioncriteria. The data collected is patient satisfaction with therapy services using the PSQ-18 questionnaire and therapeutic compliance with the MARS-5 questionnaire. The data obtained were then analyzed usingFisher's test. The results showed that of the 96 respondents, 89.6% were satisfied, 10.4% were dissatisfied with the health services obtained at Wonosari Hospital, 61.5% were compliant, and 38.5% were not compliant with their treatment. Fisher's analysis showed a significant relationship between patient satisfaction and adherence totherapy in hypertension patients with p = 0.000 (p <0.05). This study concludes that a meaningful relationship exists between satisfaction with therapy services and adherence to therapy in outpatient hypertension patients at Wonosari Hospital.